DNA barcoding of exuviae for species identification of Central European damselflies and dragonflies (Insecta: Odonata) - Marcia Sittenthaler; Iris Fischer; Andreas Chovanec; Stephan Koblmüller; Oliver Macek; Helmut Sattmann; Nikolaus Szucsich; Lukas Zangl; Elisabeth Haring (Journal of Insect Conservation, 2023)
Monitoring of odonates has become an important instrument for ecological status assessment of (semi-)aquatic habitats. Besides information on presence and abundance, knowledge about a species´ autochthony at the surveyed waterbody is a significant information within the assessment process. Here, the finding of exuviae represents the ultimate proof of successful reproduction. Although feasible for most odonate species, morphological identification of exuviae is often time consuming, as it relies on small, fragile structures. To facilitate species identification of exuviae, a DNA barcoding approach was developed, including (1) non-destructive extraction of DNA using whole exuviae or their tracheal tubes, and (2) primer systems for long (< 600 bp) and short (< 200 bp) CO1 fragments. A total of 85 exuviae from 33 species were analysed and compared to results of morphological identification. Additionally, factors potentially influencing DNA quality and quantity, as well as PCR and sequencing success were investigated. Eighty-two exuviae matched the morphologically identified genus, and 60 matched at species level. Of the 33 species present in the data set, 82% could be identified to species level via DNA barcoding. The results show how DNA-based approaches can support fast and accurate species identification and therefore enhance monitoring of an ecologically important taxonomic group, with high relevance for conservation and habitat restoration. Moreover, the use of exuviae as DNA resource once more shows that non-invasive sampling offers great potential for molecular species identification, which is essential when studying rare and endangered species. Implications for insect conservation Our results show how molecular tools, here DNA barcoding of odonate exuviae, can support species monitoring without the need of catching individuals, harming, or even killing them. Obtaining DNA from non-invasive sources can thus be a direct advantage to the conservation of insects, especially when dealing with rare and endangered species and/or populations. Using the example of odonates as bioindicator organisms for aquatic and semi-aquatic habitats, we highlight the importance of non-invasive genetic approaches for population studies and monitoring of insect species and/or species communities for ecosystem assessments and conservation management.